Social dimensions and educational values of popular proverbs - Bouzid, RAHMOUNE (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The popular proverb makes it possible to express the prevailing thought of the constituent classes of society through the experiences and that they have gone through and formulated in those short phrases that summarise an event or experience that has its social dimensions, educational values ​​and human attitude related to ways of life and its cultural data throughwhich the individualcan express his reality. Talking about the interaction of these dimensions and values ​​with in their contexts to which they belong reveals in a way the importance of proverbs and their role in maintaining the cohesion of society and its components and protecting it from the repercussions of the current and its transformations Whiles triving to proveits presence within the community system to which it belongs. and active location. This is how proverbs derived their material from society, and this is because they containits values, beliefs, and facts, and presented them from a distance to the individual as a guiding wisdom in his life. The refore, their connection to society is a close connection, and wecanclarify the image of society through proverbs and what they represent from tributaries to the wisdom of the popular person in life. This concept canexplain the importance of the trend towards studying proverbs in terms of their social dimensions and educational values, with the importance they represent in the awareness of individuals and societies, and there foreits studyis an indication of its role in popular sectors through its intellectual and cultural output. The popular proverb takes a moral character, as it calls for the values ​​of the group and the devotion of their ideals and their moral approach. We can monitor the elements of this ethical approach through the available proverbs about a group or a particular popular environment.